2017
DOI: 10.2196/cancer.6935
|View full text |Cite
|
Sign up to set email alerts
|

The Fitbit One Physical Activity Tracker in Men With Prostate Cancer: Validation Study

Abstract: BackgroundPhysical activity after cancer diagnosis improves quality of life and may lengthen survival. However, objective data in cancer survivors are limited and no physical activity tracker has been validated for use in this population.ObjectiveThe aim of this study was to validate the Fitbit One’s measures of physical activity over 7 days in free-living men with localized prostate cancer.MethodsWe validated the Fitbit One against the gold-standard ActiGraph GT3X+ accelerometer in 22 prostate cancer survivor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Collection of activity data using consumer devices has been demonstrated to be feasible and acceptable among cancer patients in active treatment 17 20 . The wearable device literature builds on early studies with older-generation research-grade accelerometers 21 , which have been shown to correlate with consumer activity tracker data in cancer patients 22 . Unlike research-grade actigraphy devices, which are costly, require specialized software to access and analyze the data, and are commonly worn for a week or less, consumer wearable devices are affordable and designed to be comfortable and convenient to wear continuously with easily recharged batteries that enable long-term data collection.…”
Section: Consumer Wearable Devices In Oncology Researchmentioning
confidence: 99%
“…Collection of activity data using consumer devices has been demonstrated to be feasible and acceptable among cancer patients in active treatment 17 20 . The wearable device literature builds on early studies with older-generation research-grade accelerometers 21 , which have been shown to correlate with consumer activity tracker data in cancer patients 22 . Unlike research-grade actigraphy devices, which are costly, require specialized software to access and analyze the data, and are commonly worn for a week or less, consumer wearable devices are affordable and designed to be comfortable and convenient to wear continuously with easily recharged batteries that enable long-term data collection.…”
Section: Consumer Wearable Devices In Oncology Researchmentioning
confidence: 99%
“…Of the 12 identified studies, only 3 evaluated activities of daily living (free living or an activity protocol) in people with a chronic disease [ 22 - 24 ]; however, these studies only tested noncommercially available activity trackers and mainly evaluated energy expenditure instead of step count. Results from other studies with participants with chronic diseases are not generalizable to daily practice because they did not have step count as the primary outcome (eg, mostly energy expenditure) [ 25 - 31 ], involved only walking and no other activities of daily living [ 32 - 35 ], or free living conditions were not protocoled (eg, cardiac patients [ 36 ] and patients with COPD [ 37 ] or cancer [ 38 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies have proven that the validity of activity trackers is generally lower at low gait speed [ 21 , 77 , 78 ]. Nevertheless, devices of the Fitbit brand have been validated for use in community-dwelling older adults [ 45 , 46 , 47 ], rehabilitation, and cancer patients [ 48 , 49 ]. Given the increasing use of activity trackers to assess PA and sedentary behavior in all age and social groups, there is a high need for further validations.…”
Section: Discussionmentioning
confidence: 99%
“…The long battery lifetime of up to 6 months makes it suitable for use in long-term studies. Recently among others, Fitbit devices have been validated for use in community-dwelling older adults [ 45 , 46 , 47 ], rehabilitation, and cancer patients [ 48 , 49 ]. Step counts are the primary measure of activity trackers.…”
Section: Methodsmentioning
confidence: 99%